Analisis Penentuan Biaya Pembuatan Akta Jual Beli Berdasarkan Aspek Akuntansi Keperilakuan Pada Kantor Notaris Dan Ppat Fita Fitriyatul Laili, Sh., M.Kn - Lailatun Nafisa; Wanda Putri Aprilia (Institut Teknologi dan Bisnis Yadika, 2025)
Notary Office And Land Deed Official Fita Fitriyatul Laili SH., M.KnIs An Office That Sells Services To Make It Easier For Clients To Buy And Sell Land And This Office Has Several Different Fee Determinations For Each Client. Due To The Differences In Taxes And Processes For Each Client, Of Course The Fita Fitriyatul Notary Office Has Thought Out A Cost Estimate That Is Almost The Same, But It Also Cannot Be Exactly The Same Due To Differences In Sales And Purchase Tax Prices Which The Notary Himself Cannot Determine. The Purpose Of This Research Is To Analyze The Determination Of Costs In Behavioral Aspects In Notary And PPAT Offices. Fita Fitriyatul Laili SH., M.Kn. This Type Of Research Is A Qualitative Method With An Interview Approach. Based On The Research Results, It Shows That Determining Fees At The Fita Fitriyatul Notary And PPAT Offices Still Has Several Obstacles, Such As The Lack Of Client Understanding Of The Price Differences That Have Been Estimated By The Offices. And It Can Be Concluded That Every Buying And Selling Transaction For Each Client May Be Different Because The Process For Each Client Is Different.